Representation of youth body images in Hilo Teen advertising (Norman Fairclough critical discourse analysis) - Hanna Sundari; Rina Husnaini Febriyanti (Universitas Indraprasta PGRI, 2018)
This research is conducted using model of Critical Discourse Analysis (CDA) that stated by Norman Fairclough. This discourse analysis is selected because it is considered to be able to answer the question of the purpose of this research that is formulated which focused on digging up the ideology value on teenager body image that is displayed on the discourse analysis in Hilo Teen advertisement. Fairclough sees a discourse as a social practice and authority which involves particular ideology value whether in explicitly or implicitly. The analysis of Fairclough is centered on text, discourse practice, and sociocultural practice. In this research, discourse analysis text Hilo Teen advertisement is focused on text dimension that involves representation, relation, and identity that is aired on the advertisement and sociocultural context in community scope. The result of this research based on the analysis defines Hilo Teen advertisement describes the body image of teenage girls are thin, slim, tall, and energetic; on the other hand, the body image of teenage boys are thin and tall. This advertisement also displays the problematic and realistic of teenagers who accentuate physical aspect only. Furthermore, Hilo Teen advertisement not only promotes milk product for teenagers but also tries forming a perception and conception on the society (teenagers and parents) about an ideal body shape of teenagers.